Suberoylanilide hydroxamic acid synergistically enhances the antitumor activity of etoposide in Ewing sarcoma cell lines. Issue 8 (September 2015) - Unland, Rebekka; Clemens, Dagmar; Heinicke, Ulrike; Potratz, Jenny C.; Hotfilder, Marc; Fulda, Simone; Wardelmann, Eva; Frühwald, Michael C.; Dirksen, Uta
<x xml:space="preserve">Abstract</x> Ewing sarcomas (ES) are highly malignant tumors arising in bone and soft tissues. Given the poor outcome of affected patients with primary disseminated disease or at relapse, there is a clear need for new targeted therapies. The HDAC inhibitor (HDACi) suberoylanilide hydroxamic acid (SAHA, Vorinostat) inhibits ES tumor growth and induces apoptosis in vitro and in vivo. Thus, SAHA may be considered a novel treatment. However, it is most likely that not a single agent but a combination of agents with synergistic mechanisms will help improve the prognosis in high-risk ES patients. Therefore, the aim of the present study was to assess a putative synergistic effect of SAHA in combination with conventional chemotherapeutic agents. The antitumor activity of SAHA in combination with conventional chemotherapeutics (doxorubicin, etoposide, rapamycin, topotecan) was assessed using an MTT cell proliferation assay on five well-characterized ES cell lines (CADO-ES-1, RD-ES, TC-71, SK-ES-1, SK-N-MC) and a newly established ES cell line (DC-ES-15). SAHA antagonistically affected the antiproliferative effect of doxorubicin and topotecan in the majority of the ES cell lines, but synergistically enhanced the antiproliferative activity of etoposide. In functional analyses, pretreatment with SAHA significantly increased the effects of etoposide on apoptosis and clonogenicity. The in-vitro analyses presented in this work show that SAHA synergistically enhances the antitumor activity of etoposide in ES cells. Sequential treatment with etoposide combined with SAHA may represent a new therapeutic approach in ES.